DAMPAK PENGGUNAAN MEDIA SOSIAL TIK-TOK TERHADAP PERILAKU MAHASISWA PROGRAM STUDI PAI SEKOLAH TINGGI AGAMA ISLAM DARUTTAQWA GRESIK - Eka Wahyu Hidayati; Devi Anggraini (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2022)
This article aims to find out, describe and analyze how the impact of the use of Tik-Tok social media on the Islamic behavior of students of the PAI Study Program at the Daruttaqwa Gresik Islamic College of Religion.  This article uses a case study approach, and is a type of qualitative research. The data collection method uses interviews, observations, and documentation. The results of the research are a) the use of Tik-Tok social media among students b) the impact of the use of TikTok social media on the form of Islamic behavior of students of the PAI Study Program of the Daruttaqwa Gresik Islamic College c) how to overcome the negative impact of the use of TikTok social media on the Islamic behavior of students of the PAI Study Program of the Daruttaqwa Gresik Islamic College. The use of Tik-Tok social media among students is that some students use it as a medium of entertainment and refreshing, looking for information quickly, a lot of scientific content, discussing events, voicing opinions, marketing products and for shopping online. The impact of using TikTok social media on students' Islamic behavior is a negative and positive impact. The positive impact is to make morals, attitudes, ways of communicating with people and manners well unaffected on Tik-Tok, make insights think broadly, provide many benefits for others, be able to manage time well and not waste productive time, TikTok also influences how to look fashionable but still follow Islamic law. Meanwhile, the negative impact of TikTok is that many students procrastinate the implementation of worship and are carried out at the end of time, for TikTok's new feature, namely TikTok Shop, students cannot control their appetite in shopping. The way to overcome the negative impact is that students must be able to have self-awareness in choosing and sorting out useful content, have self-control, manage time, restrain lust and manage money so as not to be wasteful in shopping.